2019
DOI: 10.1126/sciadv.aav8965
|View full text |Cite
|
Sign up to set email alerts
|

Tracking ultrafast hot-electron diffusion in space and time by ultrafast thermomodulation microscopy

Abstract: The ultrafast response of metals to light is governed by intriguing nonequilibrium dynamics involving the interplay of excited electrons and phonons. The coupling between them leads to nonlinear diffusion behavior on ultrashort time scales. Here, we use scanning ultrafast thermomodulation microscopy to image the spatiotemporal hot-electron diffusion in thin gold films. By tracking local transient reflectivity with 20-nm spatial precision and 0.25-ps temporal resolution, we reveal two distinct diffusion regimes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(175 citation statements)
references
References 58 publications
(70 reference statements)
12
154
0
Order By: Relevance
“…This text-book model was recently applied to model the in-plane heat transport in a nanometric metal film. [35] The thermophysical parameters used in our modeling are listed in Table 1. For an incident excitation fluence of 20 mJ cm −2 we obtain the spatio-temporal temperature maps T e/ph (z, t) of the electron and phonon systems shown in Figure 2.…”
Section: Modelingmentioning
confidence: 99%
“…This text-book model was recently applied to model the in-plane heat transport in a nanometric metal film. [35] The thermophysical parameters used in our modeling are listed in Table 1. For an incident excitation fluence of 20 mJ cm −2 we obtain the spatio-temporal temperature maps T e/ph (z, t) of the electron and phonon systems shown in Figure 2.…”
Section: Modelingmentioning
confidence: 99%
“…The first photon in this picture creates a nonequilibrium situation (hot electrons) that has to decay to the thermal equilibrium. Typical internal thermalization times of the hot electron gas in noble metals were determined to be in the range of 350 fs-3 ps [42][43][44]. Biagioni et al [19] reported on crystalline gold gap-antennas, while we study amorphous gold nanorod antennas, which will explain our shorter value of T 1 .…”
Section: The Initial Coherent Regimementioning
confidence: 62%
“…Specifically, the phonon diffusion does not change the dynamics described above (indeed, it is a much weaker effect compared with the electron-induced phonon diffusion); there is no sensitivity to the pump duration nor to the metal layer thickness. Indeed, previous studies (e.g., [35,24,26] showed that accounting for the finite thickness accounts only to modest quantitative changes in the temperature dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that a proper model for ballistic transport has to be derived from the Boltzmann equation, something that to the best of our knowledge, was not done so far. Experimentally, there have been some studies of vertical heat transport based on a configuration in which the pump and probe are incident on opposing interfaces of a metal film (see [27,28]), however, for lateral heat transport, there has been no evidence for ballistic diffusion even when using 10 femtosecond temporal resolution, see [26]. Convincing models and measurements of heat transport in this regime will also be useful for resolving arguments regarding charge transfer on the femtosecond scale which are relevant for non-thermal (the so called "hot") electron studies, and their application for photocatalysis and photodetection [4,5,52] and should eventually be combined with models of additional transport effects associated with interband transitions (see e.g., [53,54]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation